Thermodynamic equilibrium of high-carbon ferromanganese smelting - Gasik , M. M. (Theory and Practice of Metallurgy, 2026)
The goal of this study is to carry our detailed thermodynamic analysis of FeMn fluxless smelting process in submerged arc furnaces (SAF) using realistic plant data and compare the calculation results with industrial outcomes. Modern thermodynamic databases FactSAGE was deployed to assess equilibria inside separate phases and between them at 1400-1800°C for two FeMn78 alloys with different phosphorus content. Phases (metal, slag and gas) compositions were calculated with metal recovery value for manganese as well as through-recovery of manganese in both working slag and metal. It was found that temperature of the process 1500-1525°C predicts maximal recovery of manganese into the alloy. The outcomes allowed combination of blended manganese agglomerates, ores, return tails to be efficiently composed and converted into materials streams, which can be fed into the thermodynamic calculations. Such approach allows flexibility to optimize different scenarios in high-carbon ferromanganese fluxless smelting. The correlation of the calculations with industrial plant outcomes was found to be very good. The method gives a good basis to check behavior of different components and elements in the furnace, distribution of them between the phases (gas, metal, slag) and identify the pathways for improvement of the process leading to higher yield and quality. With the same thermodynamic database parameter similar approach can be used for other manganese ferroalloys.